New Paths and Policies towards Conflict Prevention Chinese and Swiss Perspectives - Fung, Courtney J.; Gehrmann, Björn; Madenyika, Rachel F.; Tower, Jason G. (Studies in Conflict, Development and Peacebuilding, 2021)
"This book explores the discourse on conflict prevention and peacebuilding by bringing together researchers from China and Switzerland over a series policy dialogues. The Charter of the United Nations, adopted in the immediate aftermath of World War II, is clear about the fundamental necessity for the international community to act in partnership to prevent violent conflict. Given recent shifts in global power dynamics, there is an apparent need for international policy issues to be addressed in ways that are inclusive of a wider variety of perspectives and approaches. Chinese policy actors are increasingly interested in fostering their own discourse on issues of prevention and peacebuilding, rooted in Chinese experience, and engaging with peers from other contexts. The chapters in this volume explore the rationale for conflict prevention and review prevailing academic and practitioner discourses on fundamental questions such as the rationales for why conflicts should be prevented and whether 'mainstream approaches' are still relevant. This book will be of interest to students of peacebuilding, conflict resolution, Chinese politics, and International Relations."